Accelerating charge transfer to enhance H2 evolution of defect-rich CoFe2O4 by constructing a Schottky junction. Issue 90 (23rd October 2020) - Wang, Yuchao; Liu, Biao; Liu, Yi; Song, Chengye; Wang, Wenju; Li, Wenkui; Feng, Qingguo; Lei, Yongpeng
Abstract : The accelerated charge transfer via constructing a Schottky junction significantly enhanced the H2 evolution activity. Abstract : We demonstrate a charge transfer boosted hydrogen (H2 ) evolution of transition metal oxides via a Schottky junction. The FeNi and metallic defect-rich CoFe2 O4 (DCF) as well as semiconducting nitrogen-doped carbon (NC), named as FeNi/DCF/NC, possessed only 6.5% charge transfer resistance of DCF. Theoretical calculations indicate that the enhanced electron movement happened from FeNi/DCF to NC. The H2 evolution activity of FeNi/DCF/NC showed 5.8-fold improvement compared to that of DCF at the overpotential of 400 mV in 1.0 M KOH. This work provides an effective way to enhance the electrocatalytic activity of oxides for the H2 evolution reaction and related reactions.